La demanda global y los ingresos tributarios en el periodo post pandemia 2020 - 2021 - Melgarejo Mariño, David Miguel (2023)
The different economic postulates maintain that economic growth must necessarily lead to an increase in tax collection, unless the levels of informality are very high. The current doctoral thesis carries out an investigation to determine the relationship between global demand and tax income in the post-pandemic period 2020 - 2021. For this purpose, this Quantitative type, Correlational level and non-experimental design. The research concludes that Global Demand is directly related to Tax Revenue in the post-pandemic period 2020 - 2021, demonstrated with the Correlation Coefficient r = 0.861502676; and the Coefficient of Determination R2 = 0.752186860. Likewise, it has been verified that the Internal Demand determines the behavior of the Global Demand, having obtained a Correlation Coefficient r = 0.998999691; and the Coefficient of Determination R2 = 0.998000382. On the other hand, the value of Internal Demand is determined by the behavior of Private Final Consumption Expenditure, a concept that reached the amount of S/. 677,602.00 million, equal to 63.76% of the total. The analysis of Tax Revenues shows that these had a growing evolution in general terms, with the exception of the II quarter of 2020 where there was a contraction of -23.68%, because of the COVID-19 pandemic.